2024
DOI: 10.1021/acs.estlett.4c00316
|View full text |Cite
|
Sign up to set email alerts
|

A Decade of Global Atmospheric Monitoring Delivers Mixed Report Card on the Stockholm Convention

Chubashini Shunthirasingham,
Michelle Hoang,
Ying Duan Lei
et al.

Abstract: Time trends in atmospheric concentrations serve to evaluate how effective the Stockholm Convention is in reducing or eliminating environmental releases of persistent organic pollutants (POPs). Twelve years (2005−2016) of continuous monitoring with a global network of 20 sampling sites reveals that concentrations of the pesticide endosulfan began to drop coincident with its listing as POP in 2011. Concentrations of other POPs started to decrease prior to listing and during the sampling period declined very slo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Air concentrations of HCBD reported for the Chinese atmosphere are many orders of magnitude higher than these levels . Shunthirasingham et al demonstrated that increases in HCBD concentrations in the atmosphere are a global phenomenon and did not start in 2017 but had in fact been ongoing since at least 2008. HCBD is now by far the most prevalent POP in the global atmosphere.…”
Section: Apparent Complacency In Response To Increasing Releases Of U...mentioning
confidence: 99%
See 1 more Smart Citation
“…Air concentrations of HCBD reported for the Chinese atmosphere are many orders of magnitude higher than these levels . Shunthirasingham et al demonstrated that increases in HCBD concentrations in the atmosphere are a global phenomenon and did not start in 2017 but had in fact been ongoing since at least 2008. HCBD is now by far the most prevalent POP in the global atmosphere.…”
Section: Apparent Complacency In Response To Increasing Releases Of U...mentioning
confidence: 99%
“…This trend was confirmed by Fiedler et al who found ∼50% higher air concentrations of HCB globally in 2017–2019 compared to 2010/11. More than 10 years of global monitoring revealed that after a drop in HCB air concentrations between 2005 and 2008, levels have been steadily and significantly rising between 2008 and 2016 …”
Section: Apparent Complacency In Response To Increasing Releases Of U...mentioning
confidence: 99%